2013
DOI: 10.1103/physrevb.88.035415
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial strain effects on adatom surface diffusion on tungsten from first principles

Abstract: Using first-principles electronic structure calculations, the energy barriers for diffusion mechanisms of adatoms on the tungsten (W) (001) and (110) surfaces under externally-applied biaxial strain fields are determined. Adatoms move either by hopping on the surface or by an exchange process with a surface atom, which is found to be completed in one step (direct exchange), or via the formation of a surface crowdion (crowdion-mediated exchange). As a result of the compact atomic stacking, hopping is found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
4
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
3
4
2
Order By: Relevance
“…4(a), which yields an activation energy of 1.60 ± 0.24 eV for an adatom exchange and a prefactor D 0 = 0.37 (×50.2 ±1 ) × 10 −4 cm 2 /s. The data agree perfectly with the activation energy of 1.55 eV for the exchange mechanism on an unreconstructed W(100) surface, obtained from our DFT calculation, and also are in good agreement with the findings of Chen and Ghoniem [15]. The activation energy for an adatom moving via exchange on the zigzag reconstructed surface is 2.05 eV for the [110] direction and 2.11 eV for the [1−10] direction.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…4(a), which yields an activation energy of 1.60 ± 0.24 eV for an adatom exchange and a prefactor D 0 = 0.37 (×50.2 ±1 ) × 10 −4 cm 2 /s. The data agree perfectly with the activation energy of 1.55 eV for the exchange mechanism on an unreconstructed W(100) surface, obtained from our DFT calculation, and also are in good agreement with the findings of Chen and Ghoniem [15]. The activation energy for an adatom moving via exchange on the zigzag reconstructed surface is 2.05 eV for the [110] direction and 2.11 eV for the [1−10] direction.…”
supporting
confidence: 91%
“…For both surfaces, DFT confirmed that the leading mechanism is adatom exchange. The energetic sequence between exchange and hopping agrees with the previous findings of Chen and Ghoniem [15] performed on an unreconstructed surface.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…In order to further test the GAP for surface properties, we carried out NEB calculations for the main migration paths of adatoms on the (1 1 0) and (1 0 0) surfaces (adatom-hopping between adjacent ground state adsorption sites, and the exchange migration as discussed in e.g. [79]). The tests revealed that while the GAP reproduces the correct stable adsorption sites, the migration paths are systematically underestimated by about 20-30% compared to the DFT values from [79].…”
Section: B Surface Propertiesmentioning
confidence: 99%